Design Of Route Programming, Autonomous Maintenance Checklist To Reduce Costs For A Small Light-Duty Company - Charcape Quispe, Gianella Milagros; Ruiz Rojas, Marialaura; SOTOMAYOR BURGA, JUAN LUIS (LACCEI, 2025)
This This study addresses the problem of a transport company in Callao, Peru, which faces delays in deliveries and unscheduled mechanical failures. To mitigate these problems, two solutions were proposed: the implementation of a Route Programming Plan and an Autonomous Maintenance system. The research was carried out through an experimental design, where relevant information from the company was collected and analyzed, allowing the identification of critical areas that required attention. The simulation results showed a total benefit of $5,578.04, an Internal Rate of Return (IRR) of 22%, a Net Present Value (NVA) of $4.319.32 and a Benefit/Cost ratio (B/C) of 1.37. Route scheduling made it possible to establish standards that improved efficiency in deliveries, while autonomous maintenance encouraged the active participation of operators in the care of equipment, reducing downtime and preventing unscheduled mechanical failures.It is concluded that the implementation of these strategies not only optimizes operational processes, but also improves the profitability and sustainability of the company. The findings suggest that the adoption of standardized methodologies and a systematic approach to implementation are replicable in other companies in the light cargo transport sector, contributing to continuous improvement and competitiveness in the market.